2020
DOI: 10.1155/2020/6948650
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors Associated with Leishmaniasis in the Most Affected Provinces byLeishmania infantumin Morocco

Abstract: Background. Human leishmaniasis, both visceral and cutaneous, has been reported in Morocco for centuries and constitutes a serious public health problem. However, the evolution of this pathology depends on several factors such as ecological, socioeconomic, and climatic conditions. The risk study of the affected foci is of great value for the control and surveillance of this endemic disease, especially in the provinces where Leishmania infantum predominates. Methods. This study concerned nine provinces located … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…This shows a sharp increase in the incidence of leishmaniases in the country [ 90 ]. In 2020, a study led by Hakkour and colleagues investigated the relationship between climate and leishmaniasis in 9 provinces of Morocco [ 81 ]. Authors concluded that humidity was significant for CL and VL (caused by the species Leishmania donovani and Leishmania infantum ) whereas temperature was significant only for VL.…”
Section: Resultsmentioning
confidence: 99%
“…This shows a sharp increase in the incidence of leishmaniases in the country [ 90 ]. In 2020, a study led by Hakkour and colleagues investigated the relationship between climate and leishmaniasis in 9 provinces of Morocco [ 81 ]. Authors concluded that humidity was significant for CL and VL (caused by the species Leishmania donovani and Leishmania infantum ) whereas temperature was significant only for VL.…”
Section: Resultsmentioning
confidence: 99%
“…50,000 to 90,000 new cases are expected to occur each year [ 6 ]. Risk factors such as urbanization, humidity, altitude, rainy seasons, and socioeconomic factors should be kept in mind [ 7 ]. The case we are reporting involves a patient with fever and bicytopenia, the latter was overlooked in this encounter, and it devolved into pancytopenia, which is much more published and talked about in the research/medical community.…”
Section: Introductionmentioning
confidence: 99%
“…Many recent studies and research papers [2][3][4] suggest that the incidence of leishmaniasis is influenced by climatic variables. Therefore, prediction approaches are needed to achieve a better outcome in disease forecasting.…”
Section: Introductionmentioning
confidence: 99%